Management of spinal emergencies in patients on direct oral anticoagulants - Beynon, Christopher; Olivares-Rivera, Arturo; Gumbinger, Christoph; Younsi, Alexander; Zweckberger, Klaus; Unterberg, Andreas (World neurosurgery, 2019)
Objective - Spine surgeons increasingly encounter acute spinal pathologies in patients treated with direct oral anticoagulants (DOACs), but only limited data on the management of these patients are currently available. - Methods - We retrospectively analyzed patients who presented to our department with acute spinal pathology during treatment with DOAC and who required urgent surgical therapy. Patient characteristics and treatment modalities were studied, with specific focus on the management of hemostasis and surgical therapy. Furthermore, we analyzed 19 cases of spinal emergencies during DOAC treatment reported in the literature. - Results - A total of 12 patients were identified and included in the present analysis. Patients suffered from acute spinal cord compression caused by spinal tumor manifestation (n = 5), empyema (n = 4), degenerative spinal stenosis (n = 1), hematoma (n = 1), and vertebral body fracture/dislocation (n = 2). All patients underwent emergency surgical treatment. Prohemostatic substances were administered perioperatively in 10 patients (83%) and included administration of prothrombin complex concentrates (83%), tranexamic acid (17%), and transfusion of platelets (8%). A total of 9 patients (75%) showed postoperative improvement of neurologic symptoms, and the in-hospital mortality in this patient cohort was 17%. - Conclusions - Emergency spine surgery is feasible and should be considered in patients on treatment with DOAC. The (low) risk of intraoperative bleeding complications has to be weighed against the risk of permanent disability if surgical decompression is delayed. Administration of prothrombin complex concentrates and tranexamic acid may improve the coagulation before surgery, especially in cases of unavailable specific antidotes.